The rise of professional women in France : gender and public administration since 1830 - Clark, Linda L., 1942- (Cambridge University Press, 2000)
This history of professional women in positions of administrative responsibility illuminates women's changing relationship to the public sphere in France since the Revolution of 1789. Linda L. Clark traces several generations of French women in public administration, examining public policy and politics, attitudes towards gender, and women's work and education. Women's own perceptions and assessments of their positions illustrate changes in gender roles and women's relationship to the state. With seniority-based promotion, maternity leaves and the absence of the marriage bar, the situation of French women administrators invites comparison with their counterparts in other countries. Why has the profile of women's employment in France differed from that in the USA and the UK? This study gives unique insights into French social, political and cultural history, and the history of women during the nineteenth and twentieth centuries. It will interest scholars of European history and also specialists in women's studies.